Abnormal brain anatomical topological organization of the cognitive‐emotional and the frontoparietal circuitry in major depressive disorder. Issue 5 (November 2014) - Qin, Jiaolong; Wei, Maobin; Liu, Haiyan; Yan, Rui; Luo, Guoping; Yao, Zhijian; Lu, Qing
<x xml:space="preserve">Abstract</x> Purpose Despite the increasing understanding of major depressive disorder (MDD) using neuroimaging techniques, the topological organization of anatomical networks underlying MDD remains unclear. Methods The topological organization of brain anatomical networks was explored using complex network approaches. Diffusion tensor image data of 29 MDD patients and 30 healthy controls were collected. Network metrics such as strength, efficiency, and centrality were computed after the construction of brain anatomical networks. Between‐group differences and correlations with clinical measurements were further explored. Results Compared with the healthy controls, MDD patients exhibited widely damaged information interactions in both cognitive‐emotional circuitry and frontoparietal circuitry. Moreover, the centralities in the right prefrontal cortex involving the right middle frontal gyrus and the right gyrus rectus were negatively correlated with the duration of disease. Additionally, the centrality in the right inferior frontal gyrus (triangular part) and the efficiency in the right superior frontal gyrus (orbital part) were both positively related to the depression severity. Conclusion These findings suggest that altered connectivity involved in affective and cognitive processing procedures might contribute to the pathogenesis of MDD. Magn Reson Med 72:1397–1407, 2014. © 2013 Wiley Periodicals, Inc.